Transverse Kerker scattering governed by two nondegenerate electric dipoles and its application in arbitrary beam steering. (March 2021) - Liu, M.Q.; Zhao, C.Y.; Bao, H.
Highlights: A new mechanism to achieve novel transverse Kerker scattering has been proposed based on two nondegenerate electric dipoles. The proof-of concept demonstration is presented using a bilayer cylinder consisted of newly Weyl semimetal without any external stimulus in midinfrared region. The transverse scattering is further extended to an arbitrary direction via phase modulation with a rotated dipole obtained. A new principle for arbitrary beam steering is put forward when the rotated dipole oscillates antiphase with an extra magnetic dipole. Abstract: In this work, we propose and demonstrate that transverse Kerker scattering (TKS), previously achieved relying on simultaneous excitation of electric dipole (ED), magnetic dipole (MD), electric and magnetic quadrupoles, can also be simply realized via only two nondegenerate EDs in two-dimensional cylindrical structures. The principle indicates that, the TKS can be achieved as if two EDs oscillate antiphase with similar magnitude despite of the same nature. The proof-of-concept demonstrations are presented using core-shell structures composed of dielectric material and Weyl semimetal that possesses largely intrinsic nonreciprocity without any external stimulus. Furthermore, we generalize the TKS behavior to arbitrary directions (i.e. ϕ 0 and ϕ 0 + π ) with a rotated dipole obtained via phase modulation. By adding an extra MD to meet the fundamental Kerker condition, it is achievable to steer the beam at a specific angle of ϕ 0 ± π / 2 . The steering angle can be tailored in a wide range (i.e. − 74 ∘ ∼ 0 ∘ ) via changing either optical index of dielectric or core's filling ratio. In addition, the proposed steering property also shows temperature-dependent performance. The present work provides totally new mechanisms to realize TKS and novel TKS-based functions, i.e. arbitrary scattering elimination and beam steering, and it will also stimulate advanced researches on nonreciprocal multipole excitation and interference associated with newly Weyl semimetal with intrinsic magneto-optical response.